с уравнением
x^2+6/x^2-4=5x/4-x^2

nfedorova868 nfedorova868    2   06.09.2021 20:50    0

Ответы
annahdh annahdh  06.09.2021 22:00

Объяснение:

\frac{ {x}^{2} + 6 }{ {x}^{2} - 4} = \frac{5x}{4 - {x}^{2} }

\frac{ {x}^{2} + 6 }{(x - 2)(x + 2)} = \frac{5x}{(2 - x)(2 + x)}

\frac{ {x}^{2} + 6}{( x - 2)(x + 2)} = - \frac{5x}{(x - 2)(x + 2)}

{x}^{2} + 6 + 5x = 0

{x}^{2} + 5x + 6 = 0

d = {5}^{2} - 4 \times 6 \times 1 = 1

x1 = \frac{ - 5 + 1}{2} = - 2

x2 = \frac{ - 5 - 1}{2} = - 3

ОДЗ:

x ≠ ±2 => x1 не является корнем уравнения

ответ: -3

ПОКАЗАТЬ ОТВЕТЫ